2020
DOI: 10.1021/acs.est.0c03119
|View full text |Cite
|
Sign up to set email alerts
|

Immobilizing Pertechnetate in Ettringite via Sulfate Substitution

Abstract: Technetium-99 immobilization in low-temperature nuclear waste forms often relies on additives that reduce environmentally mobile pertechnetate (TcO 4 − ) to insoluble Tc(IV) species. However, this is a short-lived solution unless reducing conditions are maintained over the hazardous life cycle of radioactive wastes (some ∼10,000 years). Considering recent experimental observations, this work explores how rapid formation of ettringite [Ca 6 Al 2 (SO 4 ) 3 (OH) 12 •26(H 2 O)], a common mineral formed in cementit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…1(a) and 1(b)] ( Clark et al, 2008), shows potential for anion-exchange and incorporation within its structure. This has been demonstrated previously for anionic radionuclide species, such as pertechnetate (Tc VII O 4 À ), which exchanges in for sulfate in the ettringite channels (Saslow et al, 2020). Hydrotalcite-type phases (e.g.…”
Section: àsupporting
confidence: 52%
See 1 more Smart Citation
“…1(a) and 1(b)] ( Clark et al, 2008), shows potential for anion-exchange and incorporation within its structure. This has been demonstrated previously for anionic radionuclide species, such as pertechnetate (Tc VII O 4 À ), which exchanges in for sulfate in the ettringite channels (Saslow et al, 2020). Hydrotalcite-type phases (e.g.…”
Section: àsupporting
confidence: 52%
“…While it has been shown that AFt-SO 4 (i.e. ettringite) phases have capacity for the uptake of anionic species such as pertechnetate (TcO 4 À ) (Saslow et al, 2020), evidence for the same behaviour in AFm-SO 4 phases is more limited. One example is that of iodate (I À ), which has been shown to incorporate into the interlayer of AFm-SO 4 to form an AFm phase with a mixed sulfate and iodate interlayer (Aimoz et al, 2012).…”
Section: U VI -Ettringite Systemsmentioning
confidence: 99%
“…Anion substitution in ettringite can occur via reaction with surface sites (ligand exchange), replacing Al/Ca coordinated surface OH − or substituting for sulphate inside channels (isomorphic substitution) [35]. This occurs as the ettringite surfaces are negatively charged under alkaline pH range conditions and due to the column and channel-like structure of ettringite, which is composed of columns of Ca 6 [36]. The extent of channel substitution of ettringite may be inversely proportional to the difference in size and electronegativity of the oxyanion compared with SO 4 2− (0.29 Å), resulting in As(V) (0.47 Å) being likelier to be channelsubstituted with sulphur than As(III) (0.69 Å) [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the safety case for geological disposal of radioactive wastes, 99 Tc makes a significant contribution to the long term dose risk, due its long half-life (t 1/2 = 2.1 × 10 5 years), and the high solubility and poor sorption of the pertechnetate species, TcO 4 − [1][2][3] In the context of some advanced nuclear fuel reprocessing flowsheets, such as the UREX process [4], an objective is to separate and immobilise Tc in a durable glass, ceramic or metal alloy wasteform for geological disposal [5,6]. Consequently, there is considerable research directed at the synthesis and characterisation of Tc wasteforms and understanding the sorption and migration behaviour of Tc in engineered barrier systems relevant to their geological disposal [3,7].…”
Section: Introductionmentioning
confidence: 99%